FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN DIVIDEN PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - YOHANES ERYANTO; SURYANTO SURYANTO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to provide empirical evident whether insider ownership, firm size, profitability, leverage, liquidity, earnings per share and price to book ratio have significant influence of dividend policy. Sample in this research are nonfinancial companies, which are listed in Indonesian Stock Exchange over the three years period 2012 until 2014. This research used purposive sampling method. The sample of this research consist of 52 companies that meet in criteria. This research uses multiple regression analysis to find out the influence of all independent variables above to dividend policy. The result of the research showed that firm size, leverage, earnings per share and price to book ratio had a significant influence on dividend policy, while insider ownership, profitability and liquidity had no influence.